Pengaruh Motivasi Kerja dan Loyalitas Karyawan terhadap Kinerja Karyawan Studi pada PT ABC - Risma Wina Sonia; Nicko Albart (Jurnal Ekonomi Manajemen Akuntansi, 2026)
The study aims to analyze in greater depth the influence of work motivation and employee loyalty on employee performance at PT ABC. This research employs a quantitative approach with an explanatory design intended to systematically explain the relationships among variables. Data were collected through the distribution of questionnaires using a Likert scale (1–5) to employees with a minimum of one year of tenure, as they are considered to have an adequate understanding of organizational conditions. Data analysis was conducted using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method with the assistance of SmartPLS 4 software to obtain more accurate and comprehensive results. The findings indicate that all research indicators have met the established validity and reliability criteria. The structural model test shows that work motivation has a positive and significant effect on employee performance (β = 0.207; p = 0.007), and employee loyalty also has a positive and significant effect (β = 0.718; p = 0.000). The R-square value of 0.753 indicates that both variables are able to explain 75.3% of the variation in employee performance. These findings emphasize that work motivation and employee loyalty play important roles in improving performance, with loyalty being the most dominant factor influencing employee performance.